A new methodology for use by a single caregiver to bathe bedridden elderly persons using advanced mechatronic systems - Bezerra, Karolina (2019)
In the framework of this paper, we aimed to propose a methodology for giving baths to elderly, bedridden persons, when this task is performed by a single caregiver. Usually, two caregivers are required for nursing a bedridden patient, especially when certain important tasks are needed (e.g., bathing the patient), but this is not always possible. The entire study considers the primary user’s perspective—the caregiver—who is responsible for a wide range of tasks; thus, suffering physical and psychological exhaustion over time. A physical prototype has been developed for allowing caregivers to perform tests in a life-like environment, by means of the device and the methodology. This technology, therefore, will represent an important contribution to the quality of life of caregivers. Considering an increase in the share of the elderly population and the related problems that arise in daily care, this project intends to be beneficial contemporarily. The presented methodology has been successfully tested and validated.